(untitled) (Bangladesh Rice Journal, 2020)
Mechanization is a vital issue to modernize agriculture. The entrepreneurship development is imperative to provide service to the farmers at an affordable price, especially in haor areas. The study was conceived to estimate the combine harvester’s rental charge and payback period. Data were collected from 86 rice fields harvested by a whole-feed combine harvester (Model: Zoomlion) in Mithamain upazila under the Kishoreganj district representing haor area of Bangladesh. Land size, operational time, loss time, repair time, idle time, daily area coverage and constraints of harvester machine were also recorded to predict the business viability of combine harvester. The rental charge and payback period was calculated following standard protocol to make business venture profitable. The perception of farmers regarding the prospect of using combine harvester in harvesting has been recorded through personal interviews. The field capacity of combine harvester was observed as 0.20 ha hr-1. Field efficiency of combine harvester depended on the land size. The daily area coverage can be increased after careful selection of the plots. Fuel consumption was found 4.18 l ha-1. Operational consolidation is the best approach to reduce the time of movement resulting in increased daily area coverage. Seasonal use of combine harvester in one locality of the study area was observed for 22 days. The rental charge of the machine was estimated as 10,000 Tk ha-1 and payback period was 3.5 years for the area coverage of 40 ha rice fields. Farmers would be able to save 40% harvesting cost for the rental charge of Tk 10,000 ha-1. Combine harvester rental service has emerged as a viable business model in the haor basin. Whole-feed (Zoomlion model) combine harvester appeared as an effective, economical, and labour-saving harvesting machine in the haor region land tenure system. Bangladesh Rice j. 2019, 23(2): 65-75